NILAI PENDIDIKAN KARAKTER MELALUI TRADISI LISAN PAPUA - Esther Rita Embram (Balai Bahasa Provinsi Papua, 2019)
This paper is qualitative that objectively describing about character education in Papua oral tradition. The methods used informal by verbal arranged systematically. The source of the data was the munaba tradition in Waropen tribe, Tobati folktale and Teminabuan folktale. The data were collected through documentation technique and analyzed descriptively.Generally, this paper aims to publishing and to conserving Papua oral tradition. Spesifically is to deciperated of Papua oral tradition education value that can vavor of the government program to the local society character education. The benefit are in order to change the behavior and mindset that incompatible leads to the character development that is suitable with the nation civilitation.